2016
DOI: 10.5513/jcea01/17.4.1846
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of citrinin and resveratrol and their effect on Caco-2 cell growth

Abstract: The aim of this study was to use Caco-2 cells as an in vitro model of human intestinal barrier. This model was employed to investigate interaction of citrinin and resveratrol and to determine the doses that affect cell number. Citrinin (CTN) is a toxic secondary metabolite produced by fungi of the genera Penicillium, Aspergillus and Monascus. It is contaminant of cereals, grains, food and feed products. Previous studies have shown that CTN has teratogenic, nephrotoxic, hepatotoxic and embryotoxic effects. Resv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…CIT has been reported to reduce human HCT116 colon cancer cell viability after 36 h exposure at concentrations of 150 and 300 µM, with the identified LC50 being 300 µM [169]. Authors in [168] reported that CIT exposure also resulted in a decrease in Caco-2 cell viability at 399.6 and 999 µM after 48 h exposure. Cell apoptosis was induced by CIT via endoplasmic reticulum stress [169].…”
Section: In-vitro Cell Culture Systemsmentioning
confidence: 99%
“…CIT has been reported to reduce human HCT116 colon cancer cell viability after 36 h exposure at concentrations of 150 and 300 µM, with the identified LC50 being 300 µM [169]. Authors in [168] reported that CIT exposure also resulted in a decrease in Caco-2 cell viability at 399.6 and 999 µM after 48 h exposure. Cell apoptosis was induced by CIT via endoplasmic reticulum stress [169].…”
Section: In-vitro Cell Culture Systemsmentioning
confidence: 99%